A new class of carriers that transport selective cargo from the trans Golgi network to the cell surface - Wakana, Yuichi (Nature Publishing Group, 2012)
We have isolated a membrane fraction enriched in a class of transport carriers that form at the trans Golgi network (TGN) and are destined for the cell surface in HeLa cells. Protein kinase D (PKD) is required for the biogenesis of these carriers that contain myosin II, Rab6a, Rab8a, and synaptotagmin II, as well as a number of secretory and plasma membrane-specific cargoes. Our findings reveal a requirement for myosin II in the migration of these transport carriers but not in their biogenesis per se. Based on the cargo secreted by these carriers we have named them CARTS for CARriers of the TGN to the cell Surface. Surprisingly, CARTS are distinct from the carriers that transport vesicular stomatitis virus (VSV)-G protein and collagen I from the TGN to the cell surface. Altogether, the identification of CARTS provides a valuable means to understand TGN to cell surface traffic.